Analisis Prakiraan Besaran Dampak Tingkat Kebisingan pada Kegiatan Pengoperasian Gedung Perkantoran PT X Kota Surabaya - Sulton Habib Mubarok; Muhammad Abdus Salam Jawwad (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Currently, the need for office buildings in the city of Surabaya is increasing along with the development of the economy in the city of Surabaya. PT X plans to contribute to meeting these needs, namely by building an office building in the city of Surabaya. This research was designed to calculate and determine the estimated magnitude of the impact of noise levels resulting from PT X's operational activities. Based on the calculation of the estimated magnitude of the impact, it is known that the noise level at the activity location without any activity is 52.4 dB(A) with a medium environmental quality value category (scale 3) and with operational activities producing a noise level of 67.64 dB(A). with the environmental quality value category being very bad (scale 1), so that the difference in environmental quality value between the noise level with activities and the noise level without activities is 2 (Medium Negative). Meanwhile, the noise level in settlements around the activity location without any activity is 47.8 dB(A) with a medium environmental quality value category (scale 4) and with operational activities producing a noise level of 54.66 dB(A) with the category The environmental quality value is medium (scale 3), so the difference in environmental quality value between the noise level with activities and the noise level without activities is 1 (Small Negative).